2015
DOI: 10.1017/jan.2015.9
|View full text |Cite
|
Sign up to set email alerts
|

Influence of teat flow rate in commercial milk feeding systems on calf digestion and performance

Abstract: Seventy two, one day old Friesian heifer calves were fed whole milk either via regular or slow release teats on commercial calfeteria systems (Milkbar, McInnes Manufacturing Limited, Waipu, New Zealand) for 42 days. For the entire period, the consumption time for the calves fed on the regular flow rate teat calfeterias was twice as fast as for those fed using the slow teats. Meal intake was numerically higher for the calves fed milk using the slow teats. At day 42, calves on the slow teats had a strong trend … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…Diarrhea is commonly reported in conjunction with low milk temperatures (Gleeson and Fallon, 2007). In the current study, mild diarrhea was observed more often following ingestion from the large-aperture teat, indicating that a high drinking speed is unfavorable to the animals, as discussed by McInnes et al (2015). However, in 2 cases with the large opening, we classified the diarrhea as "unrelated" to treatment, meaning diarrhea was detected after inclusion but before intake of the first test meal.…”
Section: Pain Behavior and Diarrheamentioning
confidence: 51%
“…Diarrhea is commonly reported in conjunction with low milk temperatures (Gleeson and Fallon, 2007). In the current study, mild diarrhea was observed more often following ingestion from the large-aperture teat, indicating that a high drinking speed is unfavorable to the animals, as discussed by McInnes et al (2015). However, in 2 cases with the large opening, we classified the diarrhea as "unrelated" to treatment, meaning diarrhea was detected after inclusion but before intake of the first test meal.…”
Section: Pain Behavior and Diarrheamentioning
confidence: 51%
“…Farms that reported using drinking speed as an alarm for identification of sick calves had a lower (P < 0.001) annual mortality rate (mean = 2.4, SE = 0.8%; 74% of farms) than those that did not (mean = 6.6, SE = 1.1%; 36% of farms). Calf drinking speed has been previously investigated in relation to digestion and physical growth (McInnes et al, 2015). The use of drinking speed as an alarm has been described previously (Cramer et al, 2016).…”
Section: Mortalitymentioning
confidence: 99%